Bauran Pemasaran Obyek Wisata dan Pengaruhnya Terhadap Kepuasan Pengunjung Generasi Z di Pantai Papuma Jember - Agustin HP; Yuliatin Azizah (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to analyze the impact of marketing mix elements on visitor satisfaction at Papuma Beach in Jember, with a focus on Generation Z as the primary target. The marketing mix examined includes word-of-mouth promotion, location, entrance ticket prices, products and services, and available facilities. This research employs a quantitative approach using multiple linear regression analysis, along with partial and simultaneous tests to measure the influence of independent variables on visitor satisfaction. Data were collected through questionnaires distributed to 100 Generation Z respondents, as well as observations and interviews. The findings indicate that, partially, word-of-mouth promotion, location, and facilities do not significantly affect visitor satisfaction. However, ticket prices and the quality of products and services at Papuma Beach significantly influence visitor satisfaction. Simultaneously, the marketing mix affects Generation Z visitor satisfaction with a contribution of 73.5%. The main factors determining visitor satisfaction are the natural beauty, appropriate ticket pricing, and the quality of services provided. This study recommends that Papuma Beach management pay closer attention to marketing strategies aligned with Generation Z preferences and enhance the attraction of the tourist site through service innovations and facility improvements.